2002
DOI: 10.1038/nn815
|View full text |Cite
|
Sign up to set email alerts
|

Proenkephalin A gene products activate a new family of sensory neuron–specific GPCRs

Abstract: Several peptide fragments are produced by proteolytic cleavage of the opioid peptide precursor proenkephalin A, and among these are a number of enkephalin fragments, in particular bovine adrenal medulla peptide 22 (BAM22). These peptide products have been implicated in diverse biological functions, including analgesia. We have cloned a newly identified family of 'orphan' G protein--coupled receptors (GPCRs) and demonstrate that BAM22 and a number of its fragments bind to and activate these receptors with nanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
421
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(442 citation statements)
references
References 31 publications
14
421
4
Order By: Relevance
“…Without discarding a role for G protein-coupled receptors (GPCRs) (Dong et al, 2001;Lembo et al, 2002), already known to be major players in olfactory chemoreception (Firestein, 2004;Gaillard et al, 2004), the most likely candidates are members of the transient receptor potential (TRP) channel family (Clapham et al, 2001). Among them, vanilloid (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Without discarding a role for G protein-coupled receptors (GPCRs) (Dong et al, 2001;Lembo et al, 2002), already known to be major players in olfactory chemoreception (Firestein, 2004;Gaillard et al, 2004), the most likely candidates are members of the transient receptor potential (TRP) channel family (Clapham et al, 2001). Among them, vanilloid (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are proteins that are highly enriched or exclusively expressed in primary sensory neurons, because specific modulation of these targets may allow circumvent untoward effects. Recently, Mas-related G protein-coupled receptors-X1 (MRGPR-X1) 2 have been shown to be exclusively expressed in primary sensory neurons and to be activated by bovine adrenal medulla peptide-8-22 (BAM8 -22) originating from proteolytic cleavage of pro-enkephalin by pro-hormone convertases (1,2). Several studies reported activation of the G q pathway by MRGPR-X1 in overexpression systems (1,(3)(4)(5), and a recent study revealed increased pain sensation in 15 healthy volunteers after BAM8 -22 application (6).…”
mentioning
confidence: 99%
“…Recently, Mas-related G protein-coupled receptors-X1 (MRGPR-X1) 2 have been shown to be exclusively expressed in primary sensory neurons and to be activated by bovine adrenal medulla peptide-8-22 (BAM8 -22) originating from proteolytic cleavage of pro-enkephalin by pro-hormone convertases (1,2). Several studies reported activation of the G q pathway by MRGPR-X1 in overexpression systems (1,(3)(4)(5), and a recent study revealed increased pain sensation in 15 healthy volunteers after BAM8 -22 application (6). In contrast, overexpression of MRGPR-X1 in rat dorsal root ganglia (DRG) neurons resulted in BAM8 -22-mediated inhibition of voltage-gated calcium currents and activation of M-type potassium channels via G i/o proteins believed to blunt pain perception (7).…”
mentioning
confidence: 99%
“…Tissue distribution studies have shown these receptors to be expressed mainly in the small sensory neurons of the dorsal root ganglia (DRG), suggesting a role in nociception. To date, cognate ligands have been identified for five of these receptors: proenkephalin A gene products, especially BAM22 (EC 50 ϳ13 nM), have been shown to potently activate human MrgX1 (SNSR3) (9). The neuropeptide RF amides are agonists at murine MrgA1 (NPFF, EC 50 ϳ200 nM), MrgC11 (NPFF, EC 50 ϳ54 nM), and MrgA4 (NPAF, EC 50 ϳ60 nM) (10).…”
mentioning
confidence: 99%